2018
DOI: 10.1038/s41374-018-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of small GTPase activity by NME proteins

Abstract: NME proteins are reported to influence signal transduction activity of small GTPases from the Ras superfamily by diverse mechanisms in addition to their generic NDP kinase activity, which replenishes the cytoplasmic pool of GTP. Comprehensive evidence shows that NME proteins modulate the activity of Ras GTPases, in particular members of the Rho family, via binding to their major activators GEFs. Direct interaction between several NMEs and Ras GTPases were also indicated in vitro and in vivo. These modes of reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Numerous studies reported NME1 and NME2 to be associated with a number of different binding/interacting partners [34]. Both proteins have been found to interact with dynamin [24], while NME1 additionally interacts with PRUNE 1 (Prune Exopolyphosphatase 1) [35], STRAP (Serine/Threonine Kinase Receptor Associated Protein) [36], MIF (Macrophage Migration Inhibitory Factor) [37], VHL (Von Hippel-Lindau) tumor suppressor [38], tumor virus-encoded oncoprotein EBNA 1-3C (Epstein-Barr Nuclear Antigen 1-3C) [39], and a number of small GTPases [40]. NME2 was reported to interact with MDM2 (Mouse Double Minute 2 Homolog) [41], TRF1 (Telomeric Repeat Binding Factor 1) [42], ICAP1α (Integrin Cytoplasmic Domain-Associated Protein 1α) [21], and several other proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reported NME1 and NME2 to be associated with a number of different binding/interacting partners [34]. Both proteins have been found to interact with dynamin [24], while NME1 additionally interacts with PRUNE 1 (Prune Exopolyphosphatase 1) [35], STRAP (Serine/Threonine Kinase Receptor Associated Protein) [36], MIF (Macrophage Migration Inhibitory Factor) [37], VHL (Von Hippel-Lindau) tumor suppressor [38], tumor virus-encoded oncoprotein EBNA 1-3C (Epstein-Barr Nuclear Antigen 1-3C) [39], and a number of small GTPases [40]. NME2 was reported to interact with MDM2 (Mouse Double Minute 2 Homolog) [41], TRF1 (Telomeric Repeat Binding Factor 1) [42], ICAP1α (Integrin Cytoplasmic Domain-Associated Protein 1α) [21], and several other proteins.…”
Section: Introductionmentioning
confidence: 99%
“…NDPK proteins have been shown to modulate Rho GTPases that are bound to their GEFs such as Tiam-1, Dbl-1 and Lbc of Ras, which relies directly on the protein-protein interaction of NME with GEFs (Filić et al, 2018). This was further shown by performing a two-way coimmunoprecipitation using HEK293T cells and mouse brain extracts, which had showed that NME1 and Tiam1 associate with each other, which was completely independent of NDPK kinase activity.…”
Section: Nme1 and Rho Gtpasesmentioning
confidence: 95%
“…GTPases in order to regulate them. In fact, inhibition of signaling downstream of Ras was shown to be caused be NME1 (Filić et al, 2018). Examples include upregulation of regulators of Gprotein signaling families and KSR, which is a scaffold for Ras/Raf/MEK/ERK signaling pathways, by NME1.…”
Section: Nme1 and Rho Gtpasesmentioning
confidence: 99%
“…In the recent years, the most thoroughly investigated members of the NME family, NME1 and NME2 have both been reported to interact with dynamin (37). Additionally, NME1 seems to interact with prune (38), MIF (39), p53/STRAP (40), WHL (41,42) and a number of small GTPase interacting proteins (43). NME2 has been reported to interact with TRF1 (44), MDM2 (45), ICAP1a (46) and several others.…”
Section: Nme Protein Partnersmentioning
confidence: 99%